The Plan Paradox: Management Risks for Institutional Vulnerability in Synchronizing MBKM Fluidity with OBE Curriculum Rigidity - Adripen Adripen; Nur Azizah; Ferdino Wedi Sanjaya; Susi Ratna Sari; Syahrur Ramli; Febi Nuris Putra (JPI: Jurnal Pustaka Indonesia, 2025)
This research aims to explore the systemic risks and institutional vulnerabilities arising from the synchronization of Merdeka Belajar Kampus Merdeka (MBKM) fluidity with Outcome-Based Education (OBE) curriculum rigidity at UIN Mahmud Yunus Batusangkar. The primary data sources were 100 Islamic Education (PAI) students from the 2025/2026 academic year. The urgency of this study lies in the "Plan Paradox" phenomenon, where MBKM’s flexibility policies frequently clash with OBE’s accountability standards, risking pedagogical quality decline and "documentation paralysis" that may hinder student graduation. This study employed a quantitative approach with a research and development design following Plomp’s stages to ensure instrument validity and practicality. A stratified purposive sampling technique was used to select 100 respondents from a total population of 158 students. Data were collected through structured questionnaires measuring two primary variables: MBKM Fluidity (Variable X) and OBE Rigidity (Variable Y). Data analysis utilized descriptive statistics and risk probability distributions via SPSS 29 software to calculate the Institutional Vulnerability Index. The results indicate a 78% structural unreadiness rate regarding MBKM fluidity and an 85% administrative unreadiness rate concerning OBE rigidity. A critical point was identified in the documentation synchronization with national competency matrices, reaching a 95% unreadiness rate. Discussion highlights a "False Freedom" phenomenon, where students enjoy field flexibility but are overwhelmed by rigid assessment standards and the obligation to "patch" missed theoretical material, which showed a 90% unreadiness rate. The study concludes that a "Modular Rigidity" mitigation framework is necessary to balance learning innovation with curriculum integrity.